1963
DOI: 10.1021/j100801a504
|View full text |Cite
|
Sign up to set email alerts
|

INTENSITY OF THE 9 kK. BAND AND MOLECULAR ASSOCIATION IN VANADIUM TETRACHLORIDE

Abstract: NotesVol. 67 for many of the compounds in this study, it could not be positively concluded that compounds containing iron, cadmium, or lead as the B' ion, which could not be heated above the 1000-1100°t emperature range, were not ordered even though no ordering lines were visible in their ;X-ray patterns. However, for the purpose of this study compounds Containing cadmium, lead, or iron were indexed on the basis of an ~4 A. cubic perovskite unit cell with the exception of Sr(í'eo.8sNbo.j7)Os which was indexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…An electron diffraction study 3 has found the V-Cl bond distance to be 2.14 Å, and several, not entirely conclusive, infrared and Raman measurements have been made. 1,2 The frequency most relevant to this research is ν 2 (the e bending) estimated 3 to be 97 ( 9 cm -1 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…An electron diffraction study 3 has found the V-Cl bond distance to be 2.14 Å, and several, not entirely conclusive, infrared and Raman measurements have been made. 1,2 The frequency most relevant to this research is ν 2 (the e bending) estimated 3 to be 97 ( 9 cm -1 .…”
Section: Introductionmentioning
confidence: 92%
“…The VCl 4 molecule has been experimentally [1][2][3][4][5][6][7][8] and theoretically [9][10][11][12][13][14][15][16][17] studied for more than 30 years with no definite conclusion as to the degree of vibronic coupling occurring in the ground state. Tetrahedral ligand field theory splits the 2 D term of the d 1 configuration into the orbitally degenerate 2 E lower state and 2 T upper state, separated by about 1 eV.…”
Section: Introductionmentioning
confidence: 99%
“…65 Compounds of type B,H,,C,R, are now recognized to be derivatives of dihydrocarboranes (e.g., B,C,H,), and these yield carboranes on pyrolysis, the particular carborane obtained depending on conditions. 66 The structure of B4H6,C,R, ( 5 ) is considered to involve donation from the carbon-carbon n-bond to the available sp2 orbital of the apical boron atom. 67 The reaction of carboxylic acids with trialkylborons, BR,, yield dialkylboron carboxylates, e.g., Me di-n-butylboric acid with hydroxylamine gives a compound ( Bun,EONH,), which on the basis of its infrared spectrum is considered to be a 6-membered heterocycle (7), " bon-bon."…”
Section: The Typical Elementsmentioning
confidence: 99%
“…Two important reviews have concerned the kinetics and mechanism of replacement reactions of co-ordination c0mpounds,6~ and the trans-effect in metal complexes. 66 Fast-reaction techniques continue to give important results in this field. The pressure-jump method has been developed to give a useful, sensitive, and widely applicable tool for the investigation of fast chemical reactions in solution.…”
Section: O the Rotatory Dispersion Curve Of The D-( +)-[Co En3i3+mentioning
confidence: 99%